A conceptualize of cultural ecosystem service recreational benefits: A systematic review method - Chan, Kaede Lip Chung; Russel @ Andy Immit Mojiol; Kamlisa Uni Kamlun (UCTS Publisher, 2021)
A cultural ecosystem service is part of ecosystem service that beneficial human from intangible and non-consumable welfare such as recreational values. However, these kinds of intangible values are difficult to conceptualize in any framework. So, this paper aims to conceptualize the cultural ecosystem services of recreational benefits by reviewing respective journal papers. In this study, a systematic review approach applies to a total of 38 journal papers. The Common International Classification of Ecosystem Services V5.1 classification system matches the fundamental nature of this world's reality and assists with the 8-dimension value of the environment, a theory from one of the published journals. Further, the built conceptual framework shows that "preference" is the most significant factor in a conceptual framework because it can influence "truth-telling" and "honest" during answering questionnaires or decision-making. So, further study is needed on this aspect to clarify unanswered questions in this field.